2019
DOI: 10.1002/brb3.1341
|View full text |Cite
|
Sign up to set email alerts
|

Combining Prospective Acquisition CorrEction (PACE) with retrospective correction to reduce motion artifacts in resting state fMRI data

Abstract: Background Head movement in the scanner causes spurious signal changes in the blood‐oxygen‐level‐dependent (BOLD) signal, confounding resting state functional connectivity (RSFC) estimates obtained from functional magnetic resonance imaging (fMRI). We examined the effectiveness of Prospective Acquisition CorrEction (PACE) in reducing motion artifacts in BOLD data. Methods Using PACE‐corrected RS‐fMRI data obtained from 44 subjects and subdividing them into low‐ and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The PACE protocol scanner compares 3D volumes acquired in the first and second time-points of the BOLD scan, determines if any motion happened between two time points and changes the position of field-of-view before the third time-point is acquired. It has been shown that using the PACE protocol together with offline head motion correction with regressors associated with less signal loss due to head motion [32]. Preprocessing of fMRI data was completed in Analysis of Functional Neuroimages Software (AFNI).…”
Section: Preprocessingmentioning
confidence: 99%
“…The PACE protocol scanner compares 3D volumes acquired in the first and second time-points of the BOLD scan, determines if any motion happened between two time points and changes the position of field-of-view before the third time-point is acquired. It has been shown that using the PACE protocol together with offline head motion correction with regressors associated with less signal loss due to head motion [32]. Preprocessing of fMRI data was completed in Analysis of Functional Neuroimages Software (AFNI).…”
Section: Preprocessingmentioning
confidence: 99%
“…In the general linear model, a separate nuisance regressor had values of 1 and 0 at the contaminated time point and elsewhere, respectively. In previous studies, the combination of these nuisance regressors were shown to effectively remove motion-related artifacts 83,85,86 .…”
Section: Scientific Reports |mentioning
confidence: 99%
“…Volumes were marked as motion contaminated if FD jenk > 0.20 mm. If 125 volumes of data ($5 min or more) were retained, participants were not excluded, otherwise the participant was removed from the sample for not having enough data for the stable estimation of rsFC (Lanka & Deshpande, 2019). Thus, seventeen participants were removed due to gross motion.…”
Section: Data Preprocessingmentioning
confidence: 99%